2023
DOI: 10.3389/fphar.2023.1265172
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in the roles of glycyrrhizic acid in cancer therapy

Abstract: Since the first 70 years of reporting cancer chemotherapy, malignant tumors have been the second most common cause of death in children and adults. Currently, the commonly used anti-cancer methods include surgery, chemotherapy, radiotherapy, and immunotherapy. Although these treatment methods could alleviate cancer, they lead to different forms of side effects and have no particularly significant effect on prolonging the patients’ life span. Glycyrrhizic acid (GL), a native Chinese herbal extract, has a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…Glycyrrhizic acid is the main active component of TCM Glycyrrhiza uralensis Fisch . Previous studies had shown that glycyrrhizic acid had a wide range of pharmacological effects, such as anti-oxidation, anti-inflammation, anti-viral, anti-cancer, and so on ( Wang and Du, 2016 ; Sun et al, 2019 ; Asseri et al, 2022 ; Zhang Y. et al, 2023 ). In addition, many pieces of evidence had confirmed that glycyrrhizic acid could have certain improvement effects on diabetes and its related complications.…”
Section: Active Compounds From Chinese Herbs Relieve Diabetic Vasculo...mentioning
confidence: 99%
“…Glycyrrhizic acid is the main active component of TCM Glycyrrhiza uralensis Fisch . Previous studies had shown that glycyrrhizic acid had a wide range of pharmacological effects, such as anti-oxidation, anti-inflammation, anti-viral, anti-cancer, and so on ( Wang and Du, 2016 ; Sun et al, 2019 ; Asseri et al, 2022 ; Zhang Y. et al, 2023 ). In addition, many pieces of evidence had confirmed that glycyrrhizic acid could have certain improvement effects on diabetes and its related complications.…”
Section: Active Compounds From Chinese Herbs Relieve Diabetic Vasculo...mentioning
confidence: 99%
“…In fact, Gly has been shown in preclinical models to inhibit the onset and development of different types of cancer such as cervical, endometrial, colon, gastric, leukaemia, glioblastoma, lung, liver and melanoma. At the same time, it also has a synergistic action with different chemotherapeutics and is useful in reducing the adverse effects of chemotherapy, including hepatotoxicity, nephrotoxicity, genotoxicity, neurotoxicity and pulmonary toxicity [3,5,8,25,26].…”
Section: Anticancer Activity Of Glycyrrhizinic Acidmentioning
confidence: 99%
“…Both glycyrrhizinic acid and glycyrrhetinic acid have shown similar antiviral and anticancer physiological properties [3,4]. Intravenous administration of Gly has also been evaluated, although toxicity is higher than through oral administration [5]. This makes both local and oral administration of Gly potentially useful for the treatment or prevention of viral infections or cancer and may be especially useful in problems resulting from HPV infection (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Licorice is one of the most frequently used plants in traditional Eastern medicine [ 32 , 33 , 34 , 35 ]. GA has been established to be safe for food and medical applications [ 36 , 37 , 38 ] and has a wide range of biological activities such as anti-inflammation, anti-viral, and anticancer activity (see review [ 39 ]). In previous studies, it was demonstrated by various physicochemical methods that the amphiphilic nature of GA allows it to form micelles and gel nanoparticles in aqueous solutions as well as inclusion complexes with drug molecules, thereby enhancing their stability, permeability, and bioavailability [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%